(untitled) (Fiep Bulletin - online, 2014)
The main aim of the search is to identify the role of physical education in the choice of the lifestyle in 1469 students (male and female, 17-22 years) (Nuviala, 2010). Some anthropometric characteristics (BMI ), amount of physical activity (IPAQ-A), self-efficacy perception (PSE ), scholastic grades in physical education (EV – Values among 0÷10), and the gender of the teachers are been detected, in order to characterize the population and verify their (potential) role in the choice of lifestyles. This presentation, based on the results of 1469 subjects, concerns the characteristics of the students (males versus females), their opinions on physical education and the role it played in the adoption of their lifestyle. The study of the correlations among the parameters assessed and the justifications given by the students are still in progress. Males (M) show higher values than females (F) (p<0.001 for all) for Age, BMI , IPAQ-A, PSE and EV . While the great majority of students (81.2% of males and females) have a good opinion of Physical Education as they consider fun and important for their development, less than 50% considered important in the choice of lifestyle. Only 44.4% of the students (Female 39.8% - Male 49.6%; p<0.01) agree that Physical Education classes help their engage in the practice of sport during spare time. The limited percentage of student that attributes a significant role at PE in the adoption of their lifestyle should be considered in the PE guidelines and in teacher training. Data seems to confirm greater values of physical self efficacy perception and physical activity in males (Spence, 2010). The fact that males obtain better assessments of the females raises the question of whether the teachers adopt criteria for evaluating that pose males and females equally.